2006
DOI: 10.1111/j.1745-7254.2006.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of cariporide on LPC-induced expression of ICAM-1 and adhesion of monocytes to smooth muscle cells in vitro

Abstract: Aim: To explore the effects of cariporide on the expression of intercellular adhesion molecule‐1 (ICAM‐1) and the adhesion of monocytes to vascular smooth muscle cells (SMC) in vitro.Methods: Monocytes were isolated from human peripheral blood by the Ficoll‐Hypaque method. The expression of ICAM‐1 in SMC was detected by ELISA. The adhesion of monocytes to SMC was stimulated by lysophosphatidylcholine (LPC). The adhesion ratio of monocytes was assayed by measuring protein contents. The intracellular pH ([pH]i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Lysophosphatidylcholine (LPC), as a prominent phospholipid component of OxLDL, is responsible for various biological activities of OxLDL, such as regulation of adhesion molecules, NO, cytokines, and growth factors [ 25 , 31 , 33 ]. Recently, several lines of evidence showed that eNOS expression was up-regulated by LPC [ 32 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine (LPC), as a prominent phospholipid component of OxLDL, is responsible for various biological activities of OxLDL, such as regulation of adhesion molecules, NO, cytokines, and growth factors [ 25 , 31 , 33 ]. Recently, several lines of evidence showed that eNOS expression was up-regulated by LPC [ 32 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cariporide may exert anti-atherogenic effects [15, 28] by inhibiting monocyte adhesion and expression of intercellular adhesion molecule (ICAM) [29]. The potential effect of cariporide on monocytes could be mediated through NHE-1 inhibition [13, 14, 17] or another action.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, more than 100 terrain derivatives have been proposed (Wilson, 2018), consequently forming a complete system of terrain derivative in DTA research. The extraction algorithms of these terrain derivatives and their stability, efficiency, and application classification have always been the research focus of geomorphometry scholars (Li, 2006;Yang et al, 2009;Gomez et al, 2015).…”
Section: Extraction Of Terrain Derivativesmentioning
confidence: 99%